2017
DOI: 10.21037/qims.2017.05.06
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of liver fat from single-energy quantitative computed tomography scans

Abstract: Background: Studies of soft tissue composition using computed tomography (CT) scans are often semi-quantitative and based on Hounsfield units (HU) measurements that have not been calibrated with a quantitative CT (QCT) phantom. We describe a study to establish the water (H 2 O) and dipotassium hydrogen phosphate (K 2 HPO 4 ) basis set equivalent densities of fat and fat-free liver tissue. With this information liver fat can be accurately measured from any abdominal CT scan calibrated with a suitable phantom.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Adipose tissue can be measured quickly and accurately using QCT [60]. Previous studies have reported the application of QCT for the determination of ectopic fat deposition in the liver [20,61]. An animal study showed that both QCT and MRI measurements of goose liver fat were accurate and reliable compared with chemical methods in vitro [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adipose tissue can be measured quickly and accurately using QCT [60]. Previous studies have reported the application of QCT for the determination of ectopic fat deposition in the liver [20,61]. An animal study showed that both QCT and MRI measurements of goose liver fat were accurate and reliable compared with chemical methods in vitro [19].…”
Section: Discussionmentioning
confidence: 99%
“…QCT measurements of hepatic or pancreatic tissue using the Mindways spine module software were converted into percentage fat measurements using a published method for measuring liver fat and pancreatic fat by Cheng X et al and calculated using the following equation 20 - 22 :…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…QCT quantification of liver fat content will be performed using the Supplementary Tissue Measurements application of the Mindways QCT-PRO v6.0 spine module scan analysis software as described by Cheng et al (22). The slice where the right branch of the portal vein enters the liver will be chosen for the measurement.…”
Section: Measurement Of Liver Fat Contentmentioning
confidence: 99%